The effect of work-life balance as a mediator and job opportunity as moderator on turnover intention among selected corporations in Batam - Yuli Indah Fajar Dini; June Alvina; Muhammad Donal Mon (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2024)
This research aims to study the relationship between organizational reputation, occupational prestige, and HRM practices on turnover intention. In addition, this study also examines the mediating role of work-life balance and the moderating role of job opportunity in the research variables. This research falls into the category of quantitative research that adopts a purposive sampling method with a PLS-SEM data analysis technique. This study reveals that organizational reputation, HRM practices, work-life balance, and job opportunity significantly affect turnover intention. Similarly, organizational reputation and HRM practices significantly affect work-life balance. Notably, work-life balance serves as a mediator in the relationship between HRM practices and turnover intention. The population of this research is human resources of the selected corporations domiciled in the city of Batam, while the sample of this research is 435 employees. The study's findings provide recommendations for a thorough retention strategy and an all-encompassing model of turnover intention within selected corporations. It also identifies novel factors in the selected corporations in Batam City, in which organizational reputation has a significant negative effect on work-life balance. These insights can aid HR professionals, policymakers, and management in crafting an effective strategic recruitment and retention plan.